Enhanced upregulation of smooth muscle related transcripts by TGFβ2 in asthmatic (myo) fibroblasts. Issue 4 (31st January 2006) - Wicks, J; Haitchi, H M; Holgate, S T; Davies, D E; Powell, R M
Abstract : Background: Transforming growth factor beta (TGFβ) upregulates a number of smooth muscle specific genes in (myo)fibroblasts. As asthma is characterised by an increase in airway smooth muscle, we postulated that TGFβ2 favours differentiation of asthmatic (myo)fibroblasts towards a smooth muscle phenotype. Methods: Primary fibroblasts were grown from bronchial biopsy specimens from normal (n = 6) and asthmatic (n = 7) donors and treated with TGFβ2 to induce myofibroblast differentiation. The most stable genes for normalisation were identified using RT-qPCR and the geNorm software applied to a panel of 12 "housekeeping" genes. Expression of α-smooth muscle actin (αSMA), heavy chain myosin (HCM), calponin 1 (CPN 1), desmin, and γ-actin were measured by RT-qPCR. Protein expression was assessed by immunocytochemistry and western blotting. Results: Phospholipase A2 and ubiquitin C were identified as the most stably expressed and practically useful genes for normalisation of gene expression during myofibroblast differentiation. TGFβ2 induced mRNA expression for all five smooth muscle related transcripts; αSMA, HCM and CPN 1 protein were also increased but desmin protein was not detectable. Although there was no difference in basal expression, HCM, CPN 1 and desmin were induced to a significantly greater extent in asthmatic fibroblasts than in those from normal controls (p = 0.041 and 0.011, respectively). Conclusions: Although TGFβ2 induced the transcription of several smooth muscle related genes, not all were translated into protein. Thus, while TGFβ2 is unable to induce a bona fide smooth muscle cell phenotype, it may "prime" (myo)fibroblasts for further differentiation, especially if the cells are derived from asthmatic airways.